Forecasting Analysis of Production and Sales of LCGC Cars in Indonesia - Imansyah, Yahya; Imaroh, Tukhas Shilul (PT. EQUATOR SINAR AKADEMIA, 2024)
This study aims to analyze the forecasting of production and sales of LCGC cars. The population of this study is LCGC cars circulating in Indonesia, with samples of sales data wholesale, retail sales and production of LCGC cars form Toyota, Daihatsu and Honda in Indonesia. The data analysis method uses POM QM for Windows. The results found that of the 4 time series and causal forecasting methods: Trend Analysis, Moving Average, Exponential Smoothing, and Linear Regressions. The Exponential Smoothing method has the best level of accuracy, with each alpha value for Wholesale α=0.51, Retail Sales α=0.37, Production α=0.70. The implications of this research are discussed in the article.